"Hermaphrodite Reflected In Jennifer Eugenides's Middlesex (2002): A Queer Approach" - Panggah Widodo, Muhamad; Dr. Phil. Dewi Candraningrum,, S.Pd., M.Ed (2017)
ABSTRACT This research is purposes to describe about Calliope ( Cal) Helen Stephanides, an Hermaphrodites who have twice sexuality organs identification based on searching her-self of live as hermaphrodite in Middlesex's Novel author by Jennifer Eugenides . The purposing of this research are to analyze Middlesex novel using a Queer Theory. The writer using two data resources as reference there are primer data resourcs, and secondary data resource. Data primer resource is get from Middlesex novel, then secondary data resource is get from book or journal that including about hermaphrodite and queer theory Keyword: Hermaphrodite, Queer Theory, Cal, Incest